Metode Topi Anatomi dan Fisiologi dalam Meningkatkan Kognitif Mahasiswa Keperawatan - Gatot Suparmanto; Sutiyo Dani Saputro (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Anatomy and physiology courses are basic courses in the health sector that study body anatomy and the function of organ systems down to the cellular level. Anatomy and physiology courses are also mandatory courses for undergraduate nursing students. Along the way, anatomy and physiology courses have become difficult or difficult courses for students because understanding these courses requires a lot of time and effort, because they require the process of memorizing and also understanding the many functions of the human body. The academic report in the form of student grades in the anatomy and physiology course in 2019 for undergraduate nursing students at Kusuma Husada University before improvement was 55 and this result is still below the passing threshold, namely 64. So a more innovative approach is needed, namely using the learning method "Anatomy and Physiology Hat". The aim of this research is to determine the effect of the "Anatomy and Physiology Hat" method in improving students' cognitive abilities. This research used a one group pretest and posttest design. The respondents involved were 74 students. Cognitive ability data between before and after treatment were compared using the Wilcoxon test. The analysis results show the p value = 0.000. Furthermore, it was concluded that the "Anatomy and Physiology Hat" method could improve the cognitive abilities of nursing students.Keywords: anatomy and physiology; learning methods; cognitive abilities; student of nursing ABSTRAK Mata kuliah anatomi dan fisiologi merupakan mata kuliah dasar dalam bidang kesehatan yang mempelajari ilmu urai tubuh dan fungsi sistem organ sampai dengan tingkatan sel. Matakuliah anatomi dan fisiologi juga menjadi mata kuliah wajib untuk mahasiswa sarjana keperawatan. Dalam perjalanannya, mata kuliah anatomi dan fisiologi menjadi mata kuliah yang sukar atau sulit bagi mahasiswa karena untuk memahami mata kuliah ini perlu waktu dan upaya yang besar, karena membutuhkan proses manghafal dan juga memahami fungsi tubuh manusia yang begitu banyak. Laporan akademik berupa nilai mahasiswa pada mata kuliah anatomi fisiologi tahun 2019 untuk mahasiswa sarjana keperawatan Universitas Kusuma Husada sebelum perbaikan adalah 55 dan hasil ini masih di bawah nilai ambang lulus yaitu nilai 64. Sehingga perlu pendekatan yang lebih inovatif yaitu menggunakan metode pembelajaran “Topi Anatomi dan Fisiologi”. Tujuan penelitian ini adalah untuk mengetahui pengaruh metode “Topi Anatomi dan Fisiologi” dalam meningkatkan kemampuan kognitif mahasiswa. Penelitian ini menggunakan rancangan one group pretest and posttest. Responden yang terlibat adalah 74 mahasiswa. Data kemampuan kognitif antara sebelum dan sesudah perlakuan dibandingkan dengan uji Wilcoxon. Hasil analisis menunjukkan nilai p = 0,000. Selanjutnya disimpulkan bahwa metode “Topi Anatomi dan Fisiologi” dapat meningkatkan kemampuan kognitif mahasiswa keperawatan. Kata kunci: anatomi dan fisiologi; metode pembelajaran; kemampuan kognitif; mahasiswa keperawatan